Architecture competitions – a space for political contention. Socialist Romania, 1950–1956 - Popovici, Ioana Cristina (Journal of Architecture and Urbanism, 2014)
This is an account of the relationship between architecture and power in Romania during the Stalinist period. A cursory glance at Arhitectura – the only specialist magazine to resume publication after the change in regime – suggests compliance with political direction, and professional interest in translating the theoretical method of Socialist Realism into a specific, culturally localized architectural language. Architecture competitions are a medium of intersection between theory and practice, power and the profession, ideology and economy – a space where political contention based on professional knowledge becomes possible even in totalitarian regimes. Between 1950 and 1956, Arhitectura published several competitions which, far from reinforcing Socialist Realism as the dominant architectural discourse, exposed the method’s internal contradictions and utopianism. In the ensuing confusion, there emerged a creative, practice-based counter-discourse centered on previously hegemonic dialects (the ‘national’). Based in equal amounts on the pre-established dynamics of professional culture, and on the willingness and ability of the architecture field to speculate the rules of the political game, this counter-discourse gradually led to the dismantling of Socialist Realism into alternative readings of Socialist architecture.